2022
DOI: 10.1111/1748-5967.12566
|View full text |Cite
|
Sign up to set email alerts
|

GC–MS analysis of chemical constituents and determination of the total antioxidant capacity of adult powder of Periplaneta americana

Abstract: Edible insects are alternative sources of high protein. Southeast Asia, South America, Africa, and Europe have recorded edible insects and, especially in Europe and America, there are factories that produce insects as food. In some areas of China, there has also been the habit of eating insects since ancient times. Periplaneta americana is an insect with the homology of medicine and food. In recent years, its medicinal and nutritional functions have attracted extensive attention and research. Its adult powder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…The pretreatment of locusts with PAE resulted in a significant lessening of the Al accumulated in the testes. This is likely related to the chelating activity of PAE, due to the presence of several compounds with high antioxidant features along with chelation properties in relation to the nanoparticles [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pretreatment of locusts with PAE resulted in a significant lessening of the Al accumulated in the testes. This is likely related to the chelating activity of PAE, due to the presence of several compounds with high antioxidant features along with chelation properties in relation to the nanoparticles [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of a previous study [ 20 ], some PAE compounds were chosen for molecular docking analysis in order to predict the antioxidant capacity implicated in our studied extract. The compounds, 7a-Methyl-1,2,3,6,7,7a-hexahydro-5H-inden-5-one (MHI), Methyl 4,8,12-trimethyltridecanoate (MTTD), Methylenebis (2,4,6triisopropylphenylphosphine) (MTP), Propanoic acid-ethyl ester (PAE) and oleic acid- methyl ester (OAM) were subjected to molecular docking analysis using two crystal macromolecular structures and 1AR5 and 8CAT targets to probe the antioxidant activity of these ligands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the 70% alcohol extract of PA was separated and seven types of isocoumarins were obtained (see Figure 4). Among them, (3R)-methyl-6,8-dihydroxy-7-formoxyl-3,4dihydroisocoumarin ( 5), (3R)-methyl-6,8-dihydroxy-7-methyl-3,4-dihydroisocoumarin ( 6), (3R)-ethyl-6,8-dihydroxy-3,4-dihydroisocoumarin ( 7), (3S)-hydroxymethyl-6,8-dihydroxy-7methyl-3,4-dihydroisocoumarin (8) are new compounds and (3R)-ethyl-6,8-dihydroxy-7-methyl-3,4-dihydroisocoumarin ( 9), (R)-6-hydroxymellein (10), and (3R)-methyl-7-hydroxymethyl-8hydroxy-3,4-dihydroisocoumarin-6-O-β-D-glucopyranoside (11) are known compounds [49]. When the above components were tested for cytotoxic activity using the MTT method, it was found that compounds 7 and 8 were new compounds and that compound 9 had the effect of inhibiting the activity of tumor cells, i.e., Hep G2 and MCF-7 cells.…”
Section: Isocoumarinsmentioning
confidence: 99%
“…In general, their bioactive constituents exhibit stronger pharmacological effects than those of plants. As the famous representative, the insects of the family Blattidae have a long history of medicinal application, and some studies have demonstrated their antitumor [1][2][3], tissue repair [4][5][6], antibacterial [7], antiviral [8], and other pharmacological effects [9,10]. The family Blattidae belongs to Arthropoda, Insecta, Pterygota, Blattariae in entomological taxonomy, which has existed on the earth for 320 million years [11].…”
Section: Introductionmentioning
confidence: 99%